AlN template substrate and method for producing same
By optimizing the AlN template substrate with a specific sapphire substrate off-angle and using a mixed gas carrier, the substrate's step linearity and crystallinity are improved, resulting in enhanced luminous efficiency for Group III nitride semiconductor devices.
Patent Information
- Application Number
- JP2023127362
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2043-08-03
AI Technical Summary
Existing AlN template substrates used in Group III nitride semiconductor devices exhibit inadequate properties when a sapphire substrate with an off-angle of less than 0.35° is employed, leading to suboptimal light-emitting properties.
The development of an AlN template substrate with a sapphire substrate off-angle of 0.02° or more and less than 0.35°, utilizing a mixed gas of hydrogen and nitrogen as the carrier gas during epitaxial growth, and subsequent heat treatment in a nitrogen-containing atmosphere to enhance step linearity and crystallinity.
This approach results in an AlN template substrate with improved step linearity and surface flatness, leading to enhanced luminous efficiency of Group III nitride semiconductor devices.
Smart Images

Figure 0007656661000003 
Figure 0007656661000004 
Figure 0007656661000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an AlN template substrate and a manufacturing method thereof, and more particularly to an AlN template substrate capable of exhibiting excellent light emission efficiency when used in the fabrication of a Group III nitride semiconductor device, and a manufacturing method thereof. [Background technology]
[0002] Conventionally, III-nitride semiconductors made of compounds of Al, Ga, In, etc. with N have been widely used as materials for light-emitting elements or elements for electronic devices. In particular, III-nitride semiconductors made of AlGaN with an Al composition ratio of 50% or more are used as active layers (also called "light-emitting layers") of deep ultraviolet light-emitting devices (DUV-LEDs) with emission wavelengths of 300 nm or less.
[0003] Group III nitride semiconductors have high melting points and high nitrogen dissociation pressures, making bulk single crystal growth difficult. In general, Group III nitride semiconductor layers are formed by epitaxial growth on a heterogeneous sapphire substrate.
[0004] In general, the better the crystallinity of the III-nitride semiconductor layer, the better the light-emitting properties of the III-nitride semiconductor light-emitting device. It is known that epitaxial growth of a III-nitride semiconductor on a sapphire substrate as described above causes lattice mismatch between the sapphire substrate and the III-nitride semiconductor, which is one of the causes of deterioration of crystallinity. In order to alleviate the lattice distortion caused by such lattice mismatch, an AlN template substrate in which an AlN layer is epitaxially grown on a sapphire substrate has come to be used. The properties of a III-nitride semiconductor light-emitting device are affected by the properties of the surface of the AlN layer, so in recent years, various attempts have been made to improve the properties of an AlN template substrate epitaxially grown on a sapphire substrate.
[0005] For example, according to Patent Document 1, a Group III nitride semiconductor epitaxial substrate is made of a sapphire single crystal substrate having a principal surface with a crystal orientation tilted from the C-axis direction by 0.35° to 0.55°, i.e., a C-plane sapphire single crystal substrate with an off-angle of 0.35° to 0.55°, and the thickness of the AlN layer epitaxially grown on the principal surface is controlled to 0.3 μm to 0.7 μm. Heat treatment is then performed, thereby improving the crystallinity and flatness of the AlN layer epitaxially grown on the sapphire substrate.
[0006] Patent Document 2 also describes that using only hydrogen gas as the carrier gas for the raw material trimethylaluminum (TMA) gas and using only hydrogen gas as the carrier gas for ammonia gas makes it possible to promote the lateral growth of AlN crystals and improve the flatness of the surface of the AlN layer, compared to when at least one of the carrier gases is nitrogen gas or a mixture of nitrogen gas and hydrogen gas. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent Publication No. 2016-064928 [Patent Document 2] Patent Publication No. 2017-139253 Summary of the Invention [Problem to be solved by the invention]
[0008] The technology described in Patent Document 1 has improved the surface flatness and crystallinity of an AlN layer on a C-plane sapphire substrate with an off-angle of 0.35° to 0.55°. On the other hand, the characteristics of an AlN layer on a sapphire substrate having an off-angle of less than 0.35° are insufficient. However, when the back surface of the sapphire substrate is used as the light extraction surface, it may be preferable to use a sapphire substrate with an off-angle of less than 0.35°. The ultimate purpose of forming an excellent AlN layer is to improve the characteristics of a Group III nitride semiconductor layer formed on the AlN layer, and further improved technology is desired.
[0009] Therefore, an object of the present invention is to improve the characteristics of an AlN template substrate when a sapphire substrate having an off-angle of 0.02° or more and less than 0.35° is used. [Means for solving the problem]
[0010] The present inventors have intensively studied ways to solve the above problems. In Patent Document 1, crystallinity and flatness are used as evaluation parameters for the AlN template substrate, but the inventors have focused on a new parameter called step linearity and optimized it to complete an AlN template substrate with better characteristics. As proposed in Patent Document 2, it has been conventionally considered preferable to use only hydrogen gas as a carrier gas. However, through detailed studies by the present inventors, it has been found that when using a sapphire substrate with an off-angle of 0.02° or more and less than 0.35°, the step linearity can be optimized by using a mixed gas of hydrogen gas and nitrogen gas, and the light output of a light-emitting device made of a group III nitride semiconductor layer formed on an AlN layer is improved, and the present invention has been completed.
[0011] That is, the gist and configuration of the present invention are as follows. (1) An AlN template substrate comprising: a sapphire substrate; and an AlN layer formed on a primary surface of the sapphire substrate, wherein the primary surface of the sapphire substrate is a C-plane inclined at an off angle of 0.02° or more and less than 0.35°, and wherein a step linearity ratio of 90% or more is obtained by dividing a straight-line distance connecting a first contact point on one side of a ridge of a step in an AFM image of the surface of the AlN layer and an edge of the AFM image and a second contact point on the other side by a length of the ridge of the step extending from the first contact point to the second contact point.
[0012] (2) The AlN template substrate according to (1) above, wherein the AlN layer has a surface flatness Ra of 1.1 nm or less.
[0013] (3) The AlN template substrate according to (1) above, wherein the half-width of the X-ray rocking curve of the (0002) plane of the AlN layer is 100 arc seconds or less, and the half-width of the X-ray rocking curve of the (10-12) plane is 300 arc seconds or less.
[0014] (4) A method for manufacturing an AlN template substrate, comprising: a first step of epitaxially growing an AlN layer on a primary surface of a sapphire substrate; and a second step of heat-treating the AlN layer, wherein the primary surface of the sapphire substrate is a C-plane inclined at an off-angle of 0.02° or more and less than 0.35°, a carrier gas used in the first step is a mixed gas of hydrogen gas and nitrogen gas, and the heat treatment in the second step is performed in an atmosphere containing nitrogen element.
[0015] (5) The method for producing an AlN template substrate according to (4) above, wherein the temperature inside a furnace during the heat treatment in the second step is higher than the temperature inside the furnace in the first step.
[0016] (6) The method for producing an AlN template substrate according to (4) or (5) above, wherein the ratio of nitrogen gas in the carrier gas is 1% or more and 10% or less. Effect of the Invention
[0017] According to the present invention, it is possible to provide an AlN template substrate that, when used in the fabrication of a Group III nitride semiconductor device, can provide a Group III nitride semiconductor device having excellent light emission efficiency, and a method for fabricating the same. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is an AFM diagram illustrating a step linearity in the present invention. [Diagram 2] 1 is a schematic cross-sectional view illustrating an AlN template substrate according to the present invention. [Diagram 3] 1 is a flowchart illustrating a method for manufacturing an AlN template substrate according to the present invention. [Figure 4] 2 is a schematic diagram illustrating an off-angle of a sapphire substrate surface according to the present invention. FIG. [Diagram 5] FIG. 2 is a schematic diagram illustrating the crystal orientation of a sapphire single crystal. [Figure 6] FIG. 2 is a schematic diagram of an MOCVD apparatus for growing an AlN layer according to the present invention. [Figure 7] 1 is a cross-sectional view illustrating a layer structure of a light-emitting device according to an embodiment of the present invention. [Figure 8] 2 is an AFM image of the AlN template substrate in accordance with Example 1. [Figure 9] 11 is an AFM image of an AlN template substrate according to Example 2. [Figure 10] 1 is an AFM image of an AlN template substrate according to a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Prior to describing the embodiments of the present invention, the following points will be explained in advance.
[0020] <Step Straightness> The step straightness ratio in the present invention will be described with reference to FIG. 1. The step straightness ratio in the present invention is defined as a value d / L obtained by dividing the linear distance d connecting the first contact point A and the second contact point B by the length L of the step ridgeline E1 extending from the first contact point A to the second contact point B when an AFM (atomic force microscope) image of the surface of the AlN layer is acquired and the contact points between the ridgeline E1 of the step in the AFM image and the edge of the AFM image (the upper end E2 and the lower end E3 of the observation range) are respectively the first contact point A and the second contact point B. Note that FIG. 1 shows an AFM image acquired in a rectangular range of 5.0 μm×2.5 μm. The step straightness ratio in the present invention is measured in a rectangular range of 5.0 μm×2.5 μm similar to FIG. 1, using an AFM image photographed so that the linear distance d is about 2.5 μm to 2.8 μm. Then, of all the step edges E1 observed to extend from the first contact point A to the second contact point B, the edge E1 with the smallest d / L is selected, and the minimum value of d / L is calculated.
[0021] The flatness (Ra) value in this embodiment can be calculated automatically by application software attached to the AFM device based on the surface profile obtained by AFM measurement, in accordance with the provisions of JIS (B0601-2001). In the examples of this specification, the flatness was calculated by performing AFM measurement on a rectangular area of 5.0 μm × 2.5 μm.
[0022] In this embodiment, the crystallinity is evaluated by the half-width (arcsec) of the X-ray rocking curve obtained by an X-ray diffraction apparatus. The half-width may be calculated automatically by application software attached to the X-ray diffraction apparatus. In this embodiment, the (0002) plane and the (10-12) plane to be evaluated are irradiated with X-rays to evaluate their diffraction profiles. In particular, the measurement results for the (10-12) plane are an index of the threading dislocation density (mixed screw and edge-like dislocations) in the crystal. Note that the bar representing a negative number in the Miller index is expressed by placing a minus sign before the number that is a negative number.
[0023] The thickness of the AlN layer is microscopically non-uniform at the atomic size level. Therefore, in this specification, the thickness of the AlN layer refers to the thickness of the AlN layer at the center of the wafer (hereinafter referred to as the central thickness). In this embodiment, the thickness of the AlN layer is measured using an optical interference thickness measuring device, Nanometrics Nanospec M6100A, and the thickness at the center of the wafer is taken as the central thickness, and the average value of the thicknesses at 25 points equally spaced on the wafer surface is taken as the average thickness.
[0024] In this embodiment, the thickness of each layer of the light-emitting layer formed by epitaxial growth on the AlN template substrate can be calculated from cross-sectional observation of the grown layer by TEM-EDS (transmission electron microscope).
[0025] In this embodiment, "AlGaN" is Al a Ga 1―a N. The value of the Al composition ratio a of AlGaN in this embodiment is specified from the wavelength observed by photoluminescence measurement performed on the surface of each layer when each layer is grown. The Al composition ratio a is 0 to 1 unless otherwise specified. As a method for specifying the Al composition from the cross section of the light emitting device 100, for example, EDS (energy dispersive X-ray spectroscopy) can be used.
[0026] In the present invention, the dopant concentration is a value measured by SIMS (secondary ion mass spectrometry). In addition, in this specification, when a specific impurity such as Zn, Te, or Si is not intentionally added and the layer does not function electrically as a p-type or n-type, the layer is called "i" type or "undoped." An undoped layer may contain unavoidable impurities during the manufacturing process, and specifically, the layer has a small carrier density (e.g., 4×10 16 / cm 3 In the present specification, when the doped polymer has a molecular weight of less than 1000, the doped polymer is considered to be "undoped."
[0027] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. For convenience of explanation, the aspect ratios of the substrate and each layer are shown in Fig. 2, Fig. 3, and Fig. 4 exaggerated from the actual ratio. For simplicity of illustration, Fig. 2 and Fig. 3 do not show the off-angle θ of the sapphire substrate 10, and Fig. 4 shows an enlarged schematic diagram for explaining the off-angle θ instead.
[0028] (AlN template substrate) The AlN template substrate obtained by the present invention will be described. As shown in FIG. 2, the AlN template substrate 1 according to the present invention has an AlN layer formed on the main surface 10A of a sapphire substrate 10. The main surface 10A of the sapphire substrate 10 is characterized in that the C-plane is inclined at an off angle of 0.02° or more and less than 0.35°, and the step straightness ratio is 90% or more. The crystal axis orientation of the inclination direction in which the off angle is provided may be either the m-axis direction or the a-axis direction, but it is more preferable to set it to the m-axis direction. In addition, the off angle is preferably 0.04° or more and 0.30° or less, and more preferably 0.06° or more and 0.19° or less. The step straightness ratio is more preferably 95% or more, and the upper limit is theoretically 100%, but the step straightness ratio may be 99.9% or less in consideration of productivity. Here, the thickness of the AlN layer 20 is preferably 0.3 μm or more and 0.7 μm or less.
[0029] Furthermore, the surface flatness Ra of the AlN layer 20 is preferably 1.1 nm or less, and more preferably 0.21 nm or less.
[0030] Furthermore, it is preferable that the half width of the X-ray rocking curve of the (0002) plane of the AlN layer 20 is 100 seconds or less, and the half width of the X-ray rocking curve of the (10-12) plane is 300 seconds or less.
[0031] When the AlN template substrate 1 according to the present invention is used to fabricate a Group III nitride semiconductor device, the Group III nitride semiconductor device can have excellent light emission efficiency. Each component will be described in detail below through an embodiment of a manufacturing method for obtaining the AlN template substrate 1 and each step thereof.
[0032] <Method for manufacturing AlN template substrate> FIG. 3 is a flowchart of the method for manufacturing the above-described AlN template substrate 1. As shown in FIG. 3, the method for manufacturing the AlN template substrate 1 according to the present invention includes a first step (FIGS. 3A and 3B) of epitaxially growing an AlN layer 20 on a main surface 10A of a sapphire substrate 10, and a second step (FIG. 3C) of heat-treating the AlN layer 20 formed in the first step. Here, as described above, the main surface 10A of the sapphire substrate 10 is a surface (FIG. 4) in which the C plane is inclined at an off-angle of 0.02° or more and less than 0.35°. Θ shown in FIG. 4 is the same angle as the off-angle. Further, the carrier gas used in the first step is a mixed gas of hydrogen gas and nitrogen gas, and in the second step, the heat treatment is performed in an atmosphere containing a nitrogen element.
[0033] <<First step>> In the first step, first, as shown in FIG. 3A, a sapphire substrate 10 is prepared. Here, in the present invention, a sapphire substrate 10 having a main surface 10A which is a surface inclined at an off-angle of 0.02° or more and less than 0.35° with respect to the C plane is used. Hereinafter, in the present specification, such an inclination angle of the C plane is simply referred to as the "off-angle" or "off-angle θ" of the sapphire substrate 10. Note that the crystal axis orientation in the inclination direction for providing the off-angle θ may be either the m-axis direction or the a-axis direction, but the m-axis direction is more preferable. Here, FIG. 4 is an enlarged schematic view of the main surface 10A. The terrace width W and the step height H on the main surface 10A are appropriately determined according to the off-angle θ and the axis orientation. Note that FIG. 5 is a schematic view showing the crystal orientation of a general hexagonal sapphire single crystal, and shows the a-axis, m-axis, and C plane of the sapphire single crystal. The off-angle θ, the terrace width W, and the step height H are measured by X-ray diffraction measurement, AFM, or the like.
[0034] The sapphire substrate 10 may be manufactured according to a conventional method. The off-angle θ of the sapphire substrate 10 involves an unavoidable error in the manufacturing process of the sapphire substrate. Therefore, in the present invention, angles within an error range of 8% from the upper and lower limits of the off-angle θ are included in the scope of the present invention. Other specifications of the sapphire substrate 10, such as the thickness and width, may be appropriately designed depending on the application of the AlN template substrate 1.
[0035] Next, as shown in FIG. 3B, the AlN layer 20 is epitaxially grown on the sapphire substrate 10. Here, in the present invention, the thickness T of the AlN layer 20 is preferably 0.3 μm or more and 0.7 μm or less. The AlN layer 20 can be formed, for example, by metal organic chemical vapor deposition (MOCVD). In the present invention, when the AlN layer 20 is epitaxially grown on the sapphire substrate 10, it is preferable to use ammonia gas and liquid trimethylaluminum (TMA) as raw materials, as described later, and further, a mixed gas of hydrogen gas and nitrogen gas is used as the carrier gas. Here, in the present invention, the ratio of nitrogen gas in the carrier gas is preferably 1% or more and 10% or less. The ratio of nitrogen gas is calculated by dividing the flow rate N2 of nitrogen gas [sccm] by the flow rate (N2+H2) [sccm] of the total carrier gas.
[0036] Here, in the manufacturing method of the present invention, it is essential to use a mixture of hydrogen gas and nitrogen gas as the carrier gas. Conventionally, it was considered preferable to use only hydrogen gas as the carrier gas, but the inventors have found through intensive research that the step linearity value is increased by using a mixture of hydrogen gas and nitrogen gas, which was previously considered undesirable, and that the light output of the LED formed on the AlN layer 20 is increased, as shown in the examples described below. It is believed that the ridgeline of the step is close to a straight line, and thus the fluctuation of the Al composition in the in-plane direction in the n-type semiconductor layer and the light-emitting layer formed on the AlN layer 20 is suppressed, and the composition steepness of the interface in the light-emitting layer is improved, thereby improving the light-emitting efficiency.
[0037] The growth temperature of the AlN layer 20 is preferably 1270° C. or higher and 1350° C. or lower, and more preferably 1290° C. or higher and 1330° C. or lower. This temperature range can reliably improve the crystallinity of the AlN layer 20 after heat treatment in the subsequent second step. The growth pressure in the chamber is not intended to be limited, but can be, for example, 5 Torr to 20 Torr, and more preferably 8 Torr to 15 Torr.
[0038] Furthermore, the molar ratio of group V element to group III element (hereinafter referred to as V / III ratio) calculated based on the growth gas flow rates of group V element gas such as ammonia (NH3) gas and group III element gas such as trimethylaluminum (TMA) gas is not intended to be limited, but may be, for example, in the range of 130 to 190, and more preferably in the range of 140 to 180. Note that since there is an appropriate V / III ratio depending on the growth temperature and growth pressure, it is preferable to appropriately set the growth gas flow rate.
[0039] With reference to FIG. 6, an MOCVD apparatus 50 used for epitaxially growing the AlN layer 20 will be described. In the MOCVD apparatus 50, a source material and a carrier gas are respectively supplied to a reactor 55 from an ammonia gas supply source 51, a nitrogen gas supply source 52, a hydrogen gas supply source 53, and a TMA supply source 54. Since TMA is bubbled using hydrogen gas, the hydrogen gas supply source 53 is connected to the TMA supply source 54, and hydrogen gas, TMA gas vaporized by bubbling, and nitrogen gas join at the outlet of the TMA supply source 54 and are supplied to the reactor 55. In this embodiment, a method of bubbling TMA with hydrogen gas is adopted, but the method of mixing the source material and the carrier gas is not limited to this. Furthermore, ammonia gas is supplied to the reactor 55 together with a mixed gas of nitrogen gas and hydrogen gas. The reactor 55 includes a susceptor for placing the sapphire substrate on which the AlN layer 20 is grown, support legs for supporting and rotating the susceptor, and a heater located directly below the susceptor, and can adjust the temperature and pressure inside the reactor 55 to epitaxially grow the AlN layer 20. A vacuum pump 56 for discharging gas inside the reactor is connected to the outside of the reactor 55 to the MOCVD apparatus 50.
[0040] <<Second process>> In the subsequent second step, the AlN layer 20 on the sapphire substrate 10 obtained as described above is preferably subjected to a heat treatment at a temperature higher than the growth temperature in the first step. The heat treatment is performed in an atmosphere containing nitrogen elements so as to prevent the decomposition of the AlN layer 20. The nitrogen element-containing atmosphere may have a nitrogen partial pressure higher than the nitrogen partial pressure at which AlN decomposes at the heating temperature described below. The gas used in the above atmosphere may be nitrogen gas or ammonia gas, but nitrogen gas is preferable. This heat treatment can be performed using a known heat treatment furnace. The heat treatment at high temperature can reduce the half-width of the X-ray rocking curve of the (0002) plane and the half-width of the X-ray rocking curve of the (10-12) plane of the AlN layer 20 after the heat treatment. The above-mentioned nitrogen element-containing atmosphere may contain a gas containing oxygen elements to control the decomposition of sapphire (Al2O3).
[0041] In the second step, in order to improve the crystallinity of the AlN layer 20, it is preferable to perform heat treatment at a temperature higher than the growth temperature in the first step, but it is more preferable to set the heating temperature during heat treatment at 1580°C or higher and 1730°C or lower. This is because a temperature of 1580°C or higher can sufficiently reduce the dislocation density, and a temperature of 1730°C or lower can suppress the phenomenon in which a part of the AlN layer on the surface decomposes, causing the surface to become rough. In addition, by setting the heat treatment temperature at 1600°C or higher and 1700°C or lower, the crystallinity of the AlN layer 20 can be reliably improved.
[0042] The heating time in this step is preferably 3 hours or more and 12 hours or less. Heat treatment for 3 hours or more can sufficiently reduce the dislocation density. Furthermore, a heat treatment time of 12 hours or less can suppress the phenomenon in which a part of the AlN on the surface decomposes and the surface becomes rough. In order to reliably improve the crystallinity of the AlN layer 20, it is more preferable to set the heat treatment time to 4 hours or more and 10 hours or less.
[0043] (Light emitting element on AlN template substrate) 7, the light emitting device 100 formed on the fabricated AlN template substrate 1 will be described. For example, the light emitting device 100 can be formed on the AlN template substrate 1 by sequentially forming an undoped first buffer layer 101, a second buffer layer 102, an n-type semiconductor layer 103, an n-type guide layer 104, a light emitting layer 105, an i-type guide layer 106, a p-type electron blocking layer 107, a p-type cladding layer 108, and a p-type contact layer 109 on the AlN layer 20. Each layer constituting the light emitting device 100 will be described below.
[0044] The first buffer layer 101 and the second buffer layer 102 are layers in which AlGaN layers with different Al compositions are stacked, and it is preferable that the thickness of the first buffer layer 101 is 10 nm or more and 100 nm or less, and the thickness of the second buffer layer 102 is 500 nm or more and 2000 nm or less. It is also preferable that the first buffer layer 101 and the second buffer layer 102 are undoped. The first buffer layer 101 and the second buffer layer 102 are located between the AlN layer 20 and the n-type semiconductor layer 103, which have different lattice constants, so that the n-type semiconductor layer 103 can be formed to be flat and have good crystallinity, and also have the effect of relaxing the distortion caused by the difference in lattice constant between the AlN layer 20 and the n-type semiconductor layer 103. It is also preferable that the Al composition of the second buffer layer 102 is lower than that of the first buffer layer 101.
[0045] The n-type semiconductor layer 103 is an Al x Ga 1-x The doping element is preferably N. Here, examples of the doping element include Si, Te, S, Ge, Sn, and Se. The impurity concentration when SIMS analysis was performed was 1.0×10 18 / cm 3 Above 5.0×10 19 / cm 3 It is preferable that the temperature is about the same or less.
[0046] The average surface roughness (Ra) in a rectangular area of 5.0 μm × 2.5 μm on the surface of n-type semiconductor layer 103 is preferably 1 nm or less. By having a flat surface of n-type semiconductor layer 103, the layers grown thereon can also maintain flatness.
[0047] The half-width of the X-ray rocking curve of the (10-12) plane of the n-type semiconductor layer 103 is preferably 350 seconds or less, more preferably 300 seconds or less. The Al composition ratio of the n-type semiconductor layer 103 is preferably 0.2 to 0.35, which is greater than the Al composition ratio w of the well layer 1052 described below and is greater than w <xである。
[0048] The thickness of the n-type semiconductor layer 103 may be sufficient to supply carriers, and is preferably, for example, 300 nm or more and 3000 nm or less.
[0049] As described later, an n-type electrode 192 is formed on a portion of the exposed n-type semiconductor layer 103. As a modification, an AlGaN layer having an Al composition lower than that of the n-type semiconductor layer 103 and ranging from 0 to 0.2 may be provided between the n-type semiconductor layer 103 and the n-type electrode 192.
[0050] On the n-type semiconductor layer 103, an n-type guide layer 104 may be formed, which is a layer that functions as an n-type semiconductor by containing an n-type dopant in AlGaN having the same Al composition ratio as the n-type semiconductor layer 103, and is thinner than the n-type semiconductor layer 103. Here, examples of the doped element include Si, Te, S, Ge, Sn, and Se. The thickness of the n-type guide layer 104 is preferably 10 nm or more and 300 nm or less.
[0051] The light emitting layer 105 is preferably a layer including a layer made of AlGaN. In this embodiment, the light emitting layer 105 has a plurality of barrier layers 1051 and a plurality of well layers 1052, and is illustrated as a multiple quantum well layer in which these are alternately stacked, but the light emitting layer 105 may have a single layer structure. In this embodiment, the light emitting layer 105 has well layers 1052 and barrier layers 1051 having an Al composition ratio corresponding to the central emission wavelength, and is preferably configured to have one or more pairs of combinations of the barrier layers 1051 and the well layers 1052 repeated.
[0052] The well layer 1052 of this embodiment is an Al well having an Al composition ratio w. w Ga 1-wIt is preferable that the well layer 1052 is a layer made of N. For example, when the central emission wavelength exceeds 320 nm, the Al composition ratio w is preferably w<0.3. When the central emission wavelength is 331 nm or more, it is preferable that w≦0.15. When the central emission wavelength is 349 nm or less, it is preferable that 0.07≦w. The film thickness of the well layer 1052 is preferably 1 nm or more and 5 nm or less, and it is preferably undoped.
[0053] The barrier layer 1051 is an Al layer having an Al composition ratio b. b Ga 1-b It is preferable that the barrier layer 1051 is a layer made of N. It is preferable that the Al composition ratio b of the barrier layer 1051 is in the range of w+0.05≦b≦w+0.3. The barrier layer 1051 may be undoped or may be an n-type layer containing an n-type dopant. In this case, examples of the doped element include Si, Te, S, Ge, Sn, and Se.
[0054] The i-type guide layer 106 is preferably made of AlGaN having a higher Al composition ratio than the barrier layer 1051 and is an i-type layer having a film thickness of 0.7 nm to 1.3 nm. The Al composition ratio of the i-type guide layer 106 is preferably higher than the Al composition ratio y of the p-type electron block layer 107 described below, and is most preferably AlN.
[0055] There are two methods for manufacturing the i-type guide layer 106. One is a method of directly forming the i-type guide layer 106 having the above-mentioned thickness and Al composition. The other is a method of forming an AlGaN layer having a thickness equal to or greater than the above-mentioned thickness, and then, in the process of changing the carrier gas from nitrogen gas to hydrogen gas, a decrease in nitrogen partial pressure causes Ga in the AlGaN layer to volatilize, increasing the Al composition, resulting in the i-type guide layer 106 having the above-mentioned thickness and Al composition. Either method can be adopted in this embodiment.
[0056] The p-type electron blocking layer 107 is made of Al having an Al composition ratio y. y Ga 1-yThe dopant used here is preferably N. Examples of dopants include Mg, Zn, C, and Be. The impurity concentration when SIMS analysis was performed was 1.0×10 18 / cm 3 Above 5.0×10 19 / cm 3 It is preferable that the temperature is about the same or less.
[0057] The Al composition ratio y of the p-type electron blocking layer 107 is preferably 0.35 or more and 0.45 or less. The thickness of the p-type electron blocking layer 107 is preferably 11 nm or more and 70 nm or less. By having such an Al composition ratio and thickness, the p-type electron blocking layer 107 can suppress the deterioration of its surface roughness while fulfilling its role as an electron blocking layer and improving the light emission output. A thickness of 60 nm or less is even more preferable for improving the light emission output.
[0058] The p-type cladding layer 108 is an Al z Ga 1-z The Al composition ratio z is preferably 0.17 or more and 0.27 or less. The dopants used here include Mg, Zn, C, Be, etc. The impurity concentration when SIMS analysis was performed was 1.0×10 18 / cm 3 Above 5.0×10 19 / cm 3 It is preferable that the temperature is about the same or less.
[0059] As for the relationship between the Al composition ratio z of the p-type clad layer 108 and the Al composition ratios of other layers, it is preferable that the Al composition ratio z of the p-type clad layer 108 is less than the Al composition ratio y of the p-type electron blocking layer 107 (z < y). Also, it is preferable that the Al composition ratio z of the p-type clad layer 108 is 0.48 times or more and 0.60 times or less of the Al composition ratio y of the p-type electron blocking layer 107. Hereinafter, the ratio of the Al composition ratio z of the p-type clad layer 108 to the Al composition ratio y of the p-type electron blocking layer 107 may be referred to as the Al ratio. Further, it is also preferable that the Al composition ratio z is equal to or less than the Al composition ratio x of the n-type semiconductor layer 103 (z ≦ x). Furthermore, it is preferable that the Al composition ratio z is greater than the Al composition ratio w of the above-described well layer 1052 (w < z).
[0060] The film thickness of the p-type clad layer 108 is preferably adjusted according to the film thickness of the p-type electron blocking layer 107 as follows.
[0061] In determining the film thickness of the p-type clad layer 108, the total film thickness of the p-type electron blocking layer 107 and the p-type clad layer 108 is preferably 73 nm or more and 100 nm or less in order to achieve both high emission output and flatness. Further, for improving the emission output, the total film thickness of the p-type electron blocking layer 107 and the p-type clad layer 108 is preferably 79 nm or more.
[0062] Also, since the output tends to be larger when the film thickness of the electron blocking layer is thinner when the total film thickness of the p-type electron blocking layer 107 and the p-type clad layer 108 is constant, the film thickness of the electron blocking layer is preferably 11 nm or more and 60 nm or less as a range where the effect of improving the output becomes remarkable.
[0063] The value obtained by dividing the thickness of the p-type cladding layer 108 by the thickness of the p-type electron blocking layer 107 (hereinafter, sometimes referred to as the layer thickness ratio) should be at least 0.1 or more. In order to suppress the maximum surface roughness (Rmax) of the p-type contact layer 109, the layer thickness ratio is preferably 0.4 or more, and more preferably 0.5 or more. The upper limit of the layer thickness ratio can be 6.0 or less. Furthermore, if the layer thickness ratio is less than 0.4, the surface flatness of the p-type cladding layer 108 deteriorates and Rmax of the p-type contact layer 109 tends to increase.
[0064] By setting the Al composition ratio of p-type electron blocking layer 107 in the range of 0.35 to 0.45 and the layer thickness ratio to 0.55 or more, the maximum surface roughness of p-type contact layer 109 described below can be set to less than 6.5 nm.
[0065] The p-type contact layer 109 is preferably made of a p-type semiconductor made of GaN. Dopants used here include Mg, Zn, C, and Be. The impurity concentration when SIMS analysis was performed was 1.0×10 19 / cm 3 Above 5.0×10 21 / cm 3 It is preferable that the temperature is about the same or less.
[0066] The thickness of p-type contact layer 109 is preferably 2 nm or more and 15 nm or less. The thickness of p-type contact layer 109 is more preferably 2 nm or more and 10 nm or less. By using p-type electron blocking layer 107 and p-type cladding layer 108 as described above, the flatness of p-type contact layer 109 can be ensured even if p-type contact layer 109 is made such a thin layer.
[0067] As the n-type electrode 192, it is preferable to expose the n-type semiconductor layer 103 by dry etching, form a layer made of AlGaN having an Al composition ratio lower than that of the n-type semiconductor layer 103, the Al composition ratio being not less than 0 and not more than 0.2, on the exposed n-type semiconductor layer 103, and form the n-type electrode 192 thereon.
[0068] A known electrode may be selected as the n-type electrode 192, and may be, for example, a first metal (Ti) and a second metal (Al), or a conductive metal nitride. Here, the film thickness of the first metal of the n-type electrode 192 is preferably 10 nm or more and 50 nm or less, and the film thickness of the second metal is preferably 50 nm or more and 300 nm or less.
[0069] As the p-type electrode 195, it is preferable to select a known electrode that can be used for the p-type contact layer 109, and it is more preferable that the electrode be a reflective electrode having a reflectance of 50% or more at the central emission wavelength. As the p-type electrode 195, for example, a first metal (Ni) and a second metal (Rh), or a conductive metal nitride can be used. Here, the film thickness of the first metal of the p-type electrode 195 is preferably 5 nm or more and 10 nm or less, and the film thickness of the second metal is preferably 20 nm or more and 100 nm or less.
[0070] A known film formation method, such as a sputtering method, can be used to laminate n-type electrode 192 and p-type electrode 195. Moreover, it is preferable to use a lift-off method using a resist to form the electrode patterns of n-type electrode 192 and p-type electrode 195.
[0071] The MOCVD method may be used as the method for epitaxial growth of each layer. For epitaxial growth of each layer, it is preferable to use source gas consisting of trimethylaluminum gas (TMA gas), trimethylgallium gas (TMG gas), and ammonia gas (NH3 gas). The growth temperature is preferably 1000°C or higher and 1400°C or lower, depending on the Al composition ratio. The growth pressure in the chamber may be, for example, 10 Torr to 760 Torr. Since there is an optimal molar ratio of group V elements to group III elements (V / III ratio) depending on the growth temperature and growth pressure, it is preferable to appropriately set the flow rate of the source gas.
[0072] When singulating the wafer into individual light-emitting element 100 chips, it is preferable to remove each layer on the substrate at the intended separation position by dry etching or the like. At that time, a mesa (inclined portion) may be formed on the side of each layer. The chip size of the light-emitting element 100 may be a square, rectangle, or hexagon with a side of 200 μm to 2000 μm. Scribe or laser dicing can be used to singulate the substrate. The thickness of the substrate may be adjusted by grinding or the like before singulation.
[0073] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples in any way. EXAMPLES
[0074] [Experimental Example 1] Example 1 According to the flow chart shown in FIG. 3, the AlN template substrate according to Example 1 was manufactured. That is, first, a sapphire substrate (diameter 2 inches, thickness: 430 μm, surface orientation (0001), off-angle θ in the m-axis direction: 0.11°) was prepared (FIG. 3A). Next, an AlN layer having a central thickness of 0.60 μm was grown on the sapphire substrate by MOCVD with a growth temperature of 1330° C. and a growth pressure in the chamber of 10 Torr. The flow rates of the source gases were 250 sccm for group V gas (ammonia gas) and 43 sccm for group III gas (TMA gas). At this time, a mixed gas of hydrogen gas and nitrogen gas was used as the carrier gas, and the hydrogen gas and nitrogen gas were set to 9507 sccm and 400 sccm (the ratio of nitrogen gas in the mixed gas was 4.04%). As mentioned above, the AlN film thickness was measured at a total of 25 equally spaced locations, including the center of the wafer, using an optical interference film thickness measuring device (Nanospec M6100A; manufactured by Nanospec Corporation).
[0075] Next, the AlN template substrate after the AlN layer was formed was introduced into a heat treatment furnace, and after reducing the pressure to 10 Pa, the nitrogen gas was purged to normal pressure to create a nitrogen gas atmosphere inside the furnace, and the temperature inside the furnace was then raised to subject the AlN template substrate to a heat treatment. The heating temperature was 1620° C. and the heating time was 5 hours. In this manner, the AlN template substrate according to Example 1 was produced.
[0076] The half-width of the (10-12) X-ray rocking curve of the AlN layer of the AlN template substrate measured using an X-ray diffractometer (D8 DISCOVER AUTOWAFS; manufactured by Bruker AXS, CuKα1 radiation) was 247 seconds, and the half-width of the (0002) X-ray rocking curve was 51 seconds.
[0077] In addition, when the surface roughness of the AlN template substrate was measured in a rectangular area of 5.0 μm×2.5 μm relative to the center of the wafer using an AFM, the average surface roughness (Ra) was 0.15 nm.
[0078] On the above prepared AlN template substrate, undoped Al was deposited by MOCVD. 0.40 Ga 0.60 The first buffer layer is made of N with a thickness of 30 nm and undoped Al 0.25 Ga 0.75 A second buffer layer of 1000 nm thickness made of N was then formed. The growth temperature was 1200°C.
[0079] Next, a Si-doped n-type semiconductor layer having a thickness of 2400 nm was formed on the second buffer layer. The Si concentration of the n-type semiconductor layer was measured by SIMS and found to be 1.0×10 19 atoms / cm 3 It was.
[0080] Next, the growth temperature was changed from 1200°C to 1100°C, and undoped Al was grown on the n-type semiconductor layer. 0.25 Ga 0.75 A 25 nm thick n-type guide layer made of N was then formed. 0.25 Ga0.75 A 12 nm thick barrier layer made of N and undoped Al 0.10 Ga 0.90 The formation of a 2.4 nm-thick well layer made of N was repeated three times to form a light-emitting layer with a quantum well structure.
[0081] Next, undoped Al was deposited on the light-emitting layer (on the third well layer). 0.25 Ga 0.75 A 3-nm-thick i-type guide layer made of N was then formed. After that, while continuing to supply the group V source gas, the supply of the group III source gas was stopped, the nitrogen gas used as the carrier gas was stopped, and the carrier gas was changed to hydrogen gas. One minute after the start of the hydrogen gas supply, the supply of the group III source gas was started, and the Mg-doped Al 0.40 Ga 0.60 A p-type electron blocking layer of 22 nm thick was formed using Mg-doped AlN. 0.22 Ga 0.78 A p-type cladding layer made of N and having a thickness of 64 nm was formed, and a p-type contact layer made of Mg-doped GaN and having a thickness of 4 nm (p-type GaN contact layer) was formed thereon.
[0082] The semiconductor device formed on the AlN template substrate was analyzed using SIMS, and the Mg concentration in the p-type electron blocking layer, p-type cladding layer, and p-type contact layer was found to be 1.0×10 19 atoms / cm 3 , 5.0×10 19 atoms / cm 3 , 2.0×10 20 atoms / cm 3 It was.
[0083] In addition, estimation of the Al composition ratio by photoluminescence measurement and film thickness measurement by TEM revealed that when the carrier gas was changed after the formation of the i-guide layer, the Ga component in the i-guide layer volatilized and decomposed, resulting in an i-guide layer with a film thickness of 1.0 nm and an Al composition ratio of approximately 1.
[0084] The Al composition ratio, dopant type, and film thickness of each layer of the semiconductor layer produced in Example 1 are shown in Table 1. Here, the Al composition ratio was estimated from the wavelength observed by photoluminescence measurement, the dopant type was based on the SIMS analysis results, and the film thickness was based on the TEM measurement results.
[0085] [Table 1]
[0086] Furthermore, a mask was formed on the p-type contact layer, and mesa etching was performed by dry etching to expose a part of the n-type semiconductor layer, and then the mask on the p-type contact layer was removed.
[0087] Next, a 7 nm-thick Ni layer and a 50 nm-thick Rh layer were formed in this order on the p-type contact layer to form a reflective electrode as a p-side electrode.
[0088] Furthermore, a 20 nm-thickness Ti layer and a 150 nm-thickness Al layer were formed in this order on the exposed portion of the n-type semiconductor layer to serve as an n-type electrode.
[0089] The p-side electrode and n-type electrode were laminated using a sputtering method, and the electrode patterns were formed using a lift-off method using a resist.
[0090] Furthermore, after performing contact annealing for 10 minutes at 550° C. using an infrared lamp annealing heating device, the substrate was divided into individual rectangular elements with a chip size of 1000 μm×1000 μm using a laser scriber to fabricate ultraviolet light emitting elements (hereinafter referred to as light emitting elements) according to Example 1. After element separation, the side surface of the sapphire substrate was perpendicular to the main surface, and the thickness of the sapphire substrate was 430 μm.
[0091] Example 2 An AlN template substrate was produced in the same manner as in Example 1, except that the flow rates of hydrogen gas and nitrogen gas in step 1 were changed to 9707 sccm and 200 sccm, respectively.
[0092] (Comparative Example) An AlN template substrate was produced in the same manner as in Example 1, except that the flow rate of hydrogen gas in step 1 was changed to 9907 sccm and the flow rate of nitrogen gas was changed to 0 sccm.
[0093] 8, 9, and 10 show AFM images of a 5.0 μm × 2.5 μm rectangular area of the AlN layer surface on the AlN template substrate obtained from Example 1, Example 2, and Comparative Example, respectively. In addition, the flatness, step linearity, and crystallinity of the AlN layer surface on the AlN template substrate obtained from Example 1, Example 2, and Comparative Example were measured, and a current of 350 mA was applied to the light-emitting element stacked on this AlN template substrate using a constant current voltage source, and the light-emitting output (Po) of the total luminous flux was measured by inserting the light-emitting element into the integrating sphere so that the sapphire substrate side faces the center of the integrating sphere. The results are shown in Table 2.
[0094] [Table 2]
[0095] From the above results, it was confirmed that the step linearity of the AlN layer surface increases as the ratio of nitrogen gas in the carrier gas during AlN layer growth increases, and the light output of the light emitting device formed on the AlN template substrate increases. Although the comparative example, in which nitrogen gas is not contained in the carrier gas, has superior crystallinity compared to Example 1 and Example 2, in which nitrogen gas is contained in the carrier gas, the fact that Example 1 and Example 2 have higher light output suggests that the step linearity is an important evaluation parameter for the AlN layer.
[0096] According to the present invention, by using a mixed gas of nitrogen gas and hydrogen gas as a carrier gas when forming an AlN layer, it is possible to provide an AlN template substrate with a large step linearity and a method for manufacturing the same. [Explanation of symbols]
[0097] 1. AlN template substrate 10 Sapphire substrate 10A Principal surface of sapphire substrate 20 AlN layer 50 MOCVD equipment 51 Ammonia gas source 52 Nitrogen gas supply source 53 Hydrogen gas supply source 54 TMA Source 55 Reactor 56 Vacuum Pump 100 Light emitting element 101 First buffer layer 102 Second buffer layer 103 n-type semiconductor layer 104 n-type guide layer 105 Light-emitting layer 1051 Barrier layer 1052 Well Layer 106 i-type guide layer 107 p-type electron blocking layer 108 p-type cladding layer 109 p-type contact layer 192 n-type electrode 195 p-type electrode
Claims
1. A sapphire substrate; an AlN layer formed on a primary surface of the sapphire substrate; Equipped with a primary surface of the sapphire substrate is a C-plane inclined at an off angle of 0.06° or more and 0.19° or less; a step linearity ratio, calculated by dividing a straight-line distance connecting a first contact point on one side between a ridge of a step and an edge of the AFM image in an AFM image of the surface of the AlN layer and a second contact point on the other side by a length of the ridge of the step extending from the first contact point to the second contact point, is 90% or more, and a surface flatness of the AlN layer is 0.21 nm or less. AlN template substrate.
2. the half-width of an X-ray rocking curve of the (0002) plane of the AlN layer is 100 seconds or less, and the half-width of an X-ray rocking curve of the (10-12) plane is 300 seconds or less; The AlN template substrate of claim 1 .
3. A first step of epitaxially growing an AlN layer on a primary surface of a sapphire substrate; a second step of heat treating the AlN layer; Including, a primary surface of the sapphire substrate is a C-plane inclined at an off angle of 0.02° or more and less than 0.35°; The carrier gas used in the first step is a mixed gas of hydrogen gas and nitrogen gas, and the ratio of nitrogen gas in the carrier gas is 1% or more and 10% or less; The method for producing an AlN template substrate, wherein in the second step, the heat treatment is performed in an atmosphere containing nitrogen elements.
4. The temperature in the furnace during the heat treatment in the second step is higher than the temperature in the furnace in the first step. The method for manufacturing an AlN template substrate according to claim 3 .
Citation Information
Patent Citations
Nitride semiconductor substrate and nitride semiconductor element using the same
JP2000174395A
Method for improving crystal quality of group iii nitride crystal
JP2008028007A
Sheet transportation device and image formation device
JP2016064923A
AlN TEMPLATE SUBSTRATE AND METHOD FOR MANUFACTURING THE SAME
JP2016064928A
Method of manufacturing epitaxial substrate
JP2017139253A